Career choice of bachelor and dental professional students in Faculty of Dentistry Universitas Padjadjaran - Davavilana, Farizkha Andjani; Putri, Fidya Meditia; Suryanti, Netty (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Career choice in dentistry can provide an overview of the number of dental graduates who will pursue careers as clinicians and non-clinicians. This study aimed to describe the career choices and the influencing factors of the selected career choice of the Bachelor and profession program students. Methods: The method used was a descriptive observational study with a cross-sectional approach. The research population consists of all Bachelor and professional students at the Faculty of Dentistry, Padjadjaran University. Purposive sampling technique was used, with the inclusion criteria of active Bachelor and Profession students. The sample size was determined using the proportion estimation formula with a final sample of 286 respondents. The research instrument was an online questionnaire. Furthermore, the data obtained were analyzed using descriptive statistical analysis. Results: Clinician careers (64.6%) were the most preferred, followed by combined careers (34.6%), and non-clinician careers (0.8%). The most preferred clinician career was being a specialist (27,6%) rather than a general practice dentist (25,9%). Orthodontics specialist was the most chosen. Factors that influenced career preferences were intrinsic and extrinsic. The intrinsic factor was a great opportunity to obtain in-depth knowledge. The extrinsic factors were high earning potential, sufficient earnings to fulfill needs, and flexible working time. The majority of chosen work institutions were private hospitals (30%). Most respondents chose to work in urban areas (91%) due to accessibility and strategic reasons. Conclusion: The most preferred career choice was as clinician. Career as a specialist dentist was most desirable among those who chose to be a clinician, with the most chosen as orthodontist. The main intrinsic and extrinsic factors were a great opportunity to obtain in-depth knowledge and a high salary. Most respondents selected private hospitals and urban areas as the work location.Keyword career choice, bachelor students, profession students